Використання генетичних алгоритмів для виявлення вторгення в комп`ютерні мережі - Корниєнко, Б.Я.; Бойко, Г.О.; Снігур, О.С. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
This paper describes how it is possible to apply Genetic Algorithm in Intrusion Detection Systems. A brief overview of the Intrusion Detection System, genetic algorithm, and related detection techniques is presented. Compare with other implementations of the same problem, this implementation considers both temporal and spatial information of network connections in encoding the network connection information into rules in IDS. The main system architecture and diagram of GA are shown.